Optimalisasi Penggunaan Antibiotik: Program Edukasi dan Pemahaman Risiko Resistensi Antibiotik di SMK Swadaya Global Jakarta - Rusdi, Numlil Khaira; Maifitrianti; Nurhasnah; Listiyanti, Melly; Negara, Tigo Ramansyah Prawira; Kasianto (Yayasan Kawanad, 2024)
Antibiotic resistence is a serious global problem that can increase morbidity, mortality and medical costs. Vocational school students can act as agents of change to prevent antibiotic misuse in society. This service activity was carried out at SMK Swadaya Global School, Buaran, East Jakarta with a total of 30 participants. Education was carried out with lectures and followed by a Forum Group Discussion (FGD). Students were divided into 3 groups and each group was accompanied by a facilitator. Each group was given a case about the use of antibiotics in the community. The service activities were carried out well and students participated in the activities enthusiastically during the activities. The results of the Wilcoxon analysis showed that there was an increase in students' knowledge and attitudes towards antibiotic use after the activity (p value< 0.001).